Formulation and Evaluation of Baclofen Mucoadhesive Buccal Films - Ali, Muaadh A. Mohamed; Sabati, Ahmed Mohammed; Ali, Bassam Abduh (The Society of Pharmaceutical Sciences of Ankara, 2017)
Aim of the present work was to formulate and design mucoadhesive buccal films of baclofen (muscle relaxant) using different hydrophilic polymers and to evaluate them. The baclofen was incorporated into film that was composed of film forming and bioadhesive polymers. Hydroxypropyl methyl cellulose (HPMC) was used as film forming agent. Both Carbopol 940 (CP940) and polyvinylpyrrolidone (PVP) were used as bioadhesive polymers. Propylene glycol (PG) was used as plasticizer. Films were fabricated by solvent casting technique and then they were subjected to various evaluation parameters. Drug-excipients compatibility test was studied and no possible drug-excipients interaction. After formulation, it was observed that the formulated buccal films had appeared with satisfactory physicochemical characters except formula B3. Low values of standard deviation in thickness, weight measurement and drug content data reflected no significant difference within the batch. The in vitro mucoadhesive strength values were satisfactory for maintaining them in oral cavity except for B1 and B7 that showed the lowest values. The data clearly showed that percentage release of baclofen after 8 hours using phosphate buffer (pH 6.8). By studying and analyzing the in-vitro data pharmacokinetically for the tested formulations, it was observed that the mechanism of drug release from most films found to be non-Fickian diffusion. According to the in vivo residence time study, it was detected that formulas B4 and B6 had the highest mucoadhesion time with 4.77 and 5.07 hours, respectively. Finally, it was concluded that formulation B4 exhibited the most satisfactory results representing good physicochemical properties, in vitro profiles, and suitable mucoadhesion strength.